The Strategic Plan of the Information Technology Deanship - King Abdulaziz University- Saudi Arabia - Al-Jedibi, Wagdy (Bright Institute, 2022)
IT has now become an integral part of modern university life to the extent that various IT institutions are required to act as partners within the academic institutions rather than just providing them with secure and reliable IT infrastructure and services. Thus, in light of these successive accelerating developments, and keeping pace with the vision of the Kingdom of Saudi Arabia 2030 in relation to developing the higher education system that focuses on granting Saudi universities a great deal of administrative and financial independence, the Deanship of Information Technology at King Abdulaziz University works hard to activate its leading role in providing modern technical services for various sectors inside and outside the university through framing and preparing a new strategic vision in line with the changes taking place in the work environment at the university. Essentially, this new vision takes into account the fact that King Abdulaziz University is a research and educational institution at a global level with global interests and with constantly increasing technological environment demands that are vital to support its overall competitiveness and success. By the end of this article, the willingness of our community members to meet and engage in a deep and comprehensive discussion of the strategic strengths, weaknesses, opportunities and threats of the IT environment “based on the use of the SWOT approach” is in itself a solid evidence of our community’s excellent ability to work together towards achieving a set of common ambitious goals. Ultimately, the process of planning and designing the strategic plan allowed participants from all over the campus to interact with each other and reach a common understanding of the university’s technological goals and the strategic actions required to achieve those goals namely in relation to supporting innovation in research and education, helping people use technology more effectively, and providing secure services and systems for all the university environment components.